Comprehending The Concept Of Comparison In Early Childhood Through Block Games - Wedani, Putu; Suyanta, I Wayan (International Journal of Multidisciplinary Sciences, 2023)
Early childhood was the most crucial age in obtaining an education. In Early Childhood Education (PAUD), six development aspects need to be considered by the teacher. Those aspects included NAM, cognitive, physical motor, language, social-emotional, and art. These developments could stimulate various activities. Education in early childhood is not only about academic skills, but teachers must be able to develop children’s creativity. One of the crucial development aspects was cognitive. Children’s cognitive development could stimulate through various activities, including comparison ability. Comparison ability was an activity or comprehending comparison, both in the form of images and concrete objects. Comparison is one of the activities given to children to stimulate cognitive development. However, judging from the phenomenon in the field, the lack of teacher creativity in utilizing APE (Educational Game Tools) made the children less comprehend the concept of comparison. So, it was provided solutions by researching and comprehending the concept of comparison through block games. This study aimed to provide comprehension to B group students at Kumara Sari 1 Penarungan Kindergarten regarding the concept of comparison in early childhood through block games, as well as improving the creativity of the students and teachers. The block games aimed to develop cognitive and physical motor skills aspects in early childhood. This research was qualitative research with the model of Miles and Huberman. In this model, there were several stages conducted, including data reduction, data display, and conclusion (verification). Qualitative research must be conducted directly so that researchers can find the needed data. The data collection techniques used by researchers were observation, interviews, and documentation. This study’s primary informants or respondents were B group students, then B group class teachers and school principals. The results of this study stated that there was an improvement in the B group student comprehension at Kumara Sari I Penarungan Kindergarten regarding the concept of comparison through block games and increasing the creativity the students possessed. So, the block games could be used by the teachers to improve children’s comprehension of comparison abilities or the ability to compare objects such as concrete objects, pictures, and videos. In addition, the game tools could be used to improve students’ creativity.